Exosomes in cartilage microenvironment regulation and cartilage repair - Longfei, Han; Wenyuan, Hou; Weihua, Fang; Peng, Peng; Sun, Lu; Kun, Lin; Mincong, He; Fan, Yang; Wei, He; Qiushi, Wei (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a debilitating disease that predominantly impacts the hip, hand, and knee joints. Its pathology is defined by the progressive degradation of articular cartilage, formation of bone spurs, and synovial inflammation, resulting in pain, joint function limitations, and substantial societal and familial burdens. Current treatment strategies primarily target pain alleviation, yet improved interventions addressing the underlying disease pathology are scarce. Recently, exosomes have emerged as a subject of growing interest in OA therapy. Numerous studies have investigated exosomes to offer promising therapeutic approaches for OA through diverse in vivo and in vitro models, elucidating the mechanisms by which exosomes from various cell sources modulate the cartilage microenvironment and promote cartilage repair. Preclinical investigations have demonstrated the regulatory effects of exosomes originating from human cells, including mesenchymal stem cells (MSC), synovial fibroblasts, chondrocytes, macrophages, and exosomes derived from Chinese herbal medicines, on the modulation of the cartilage microenvironment and cartilage repair through diverse signaling pathways. Additionally, therapeutic mechanisms encompass cartilage inflammation, degradation of the cartilage matrix, proliferation and migration of chondrocytes, autophagy, apoptosis, and mitigation of oxidative stress. An increasing number of exosome carrier scaffolds are under development. Our review adopts a multidimensional approach to enhance comprehension of the pivotal therapeutic functions exerted by exosomes sourced from diverse cell types in OA. Ultimately, our aim is to pinpoint therapeutic targets capable of regulating the cartilage microenvironment and facilitating cartilage repair in OA.